2014
DOI: 10.1007/s00330-014-3140-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound point shear wave elastography assessment of liver and spleen stiffness: effect of training on repeatability of measurements

Abstract: Reproducibility of SS measurements depends on the expertise of the operator. To achieve good reproducibility between measurements a training period is required. A learning curve in pSWE acquisition should be taken into account. SS measurements are less reproducible than LS measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 26 publications
4
63
0
Order By: Relevance
“…Second, SWE of the prostate was performed by a single radiologist, and as a result, interobserver reproducibility could not be evaluated. Further studies are warranted to resolve this issue, as the degree of training has been observed to have an effect on repeatability of SWE measurements [23]. Third, although we assessed the intraobserver reproducibility using two independent and sequential measurements at the identical location, the TRUS probe was not removed and reapplied between each acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SWE of the prostate was performed by a single radiologist, and as a result, interobserver reproducibility could not be evaluated. Further studies are warranted to resolve this issue, as the degree of training has been observed to have an effect on repeatability of SWE measurements [23]. Third, although we assessed the intraobserver reproducibility using two independent and sequential measurements at the identical location, the TRUS probe was not removed and reapplied between each acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ability to visually control elasticity maps in real time and to choose the Bproper^one for LS measurement could be criticized as a potential source of subjectivity. The reliability of real-time two-dimensional (RT 2D)-SWE for the estimation of LF severity appears to be comparable to other SE methods, with somewhat better performance reported for the early stages of LF [5][6][7][8][9][10][11]. In this study, we evaluated the performance of RT 2D-SWE in a population of patients with CVH by comparing LS as obtained by RT 2D-SWE to LF stage as defined histopathologically and to cirrhosis stage defined by clinical criteria.…”
Section: Introductionmentioning
confidence: 94%
“…However, they questioned the necessity of taking ten repeated measurements, especially for good-quality examinations [3]. Moreover, the number of hepatic shear wave velocity (SWV) measurements acquired varied from three to twenty in previous studies [511]. …”
Section: Introductionmentioning
confidence: 99%